2011
DOI: 10.1002/adma.201003903
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Low Bandgap Polymer for Air‐Stable, High‐Mobility Field‐Effect Transistors and Efficient Polymer Solar Cells

Abstract: A new low bandgap polymer POD2T‐DTBT has been synthesized and found to give excellent performances in organic thin‐film transistor (OTFT) and organic photovoltaic (OPV) applications. OTFTs based on POD2T‐DTBT have achieved good hole carrier mobilities of 0.2 cm2V−1s−1 and OPVs based on blends of POD2T‐DTBT and PC71BM have demonstrated promising power conversion efficiencies of 6.26%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(56 citation statements)
references
References 20 publications
1
55
0
Order By: Relevance
“…We found that BT-or BO-based conjugated polymers are ones of the most important polymer semiconductors due to their convenient preparation, excellent thermal stability, and electronic characteristic; and many efforts have been devoted to the design and synthesis of new BT/BO derivatives [22,23]. Up to now, hole mobilities of the PFETs based on BT-containing polymers have been up to 1 cm 2 V −1 s −1 after systematic optimization [24].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…We found that BT-or BO-based conjugated polymers are ones of the most important polymer semiconductors due to their convenient preparation, excellent thermal stability, and electronic characteristic; and many efforts have been devoted to the design and synthesis of new BT/BO derivatives [22,23]. Up to now, hole mobilities of the PFETs based on BT-containing polymers have been up to 1 cm 2 V −1 s −1 after systematic optimization [24].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The J sc s and FFs of P4-P7-based devices are lower than those of P3HT:PC 61 BM-based devices (J sc : 9.5 mA cm −2 ; FF: 68 %) [53], which resulted in the lower overall PCEs. Surpassing the PCE of P3HT-based PSCs was achieved by Chen and co-workers [54], who developed a Th 4 /BT-based alternating copolymer, P8. Long and branched 2-octyldodecyl groups were used as side chains to ensure good solubility and to reach high molecular weight.…”
Section: Polythiophene-based Polymers Containing 213-benzothiadiazomentioning
confidence: 99%
“…A new polymer P52 based quaterthiophen and benzothiadiazole units were developed by Ong et al The bandgap of P52 was about 1.59 eV, and HOMO energy level of −5.18 eV. When fabricated solar with PC 71 BM, the devices demonstrated high PCEs between 5.83% and 6.26% (Table 4) [109]. Indacenodithiophene (IDT) has been paid much attention in the design of new conjugated copolymers for the application in the solar cells [110].…”
Section: Polymers Containing 213-benzothiadiazolementioning
confidence: 99%